A rare complication of middle ear cholesteatoma - Pseudoaneurysm of petrous internal carotid artery - Lim, L. Y.; Mohamad, Irfan; Lau, J. H; Tang, I. P. (Egyptian Society of Ear Nose Throat and Allied Sciences, 2017)
Objectives: To report a rare complication of middle ear cholesteatoma resulting pseudoaneurysm of petrous internal carotid artery (ICA). Case report: A 39. year old lady presented with sudden profuse bleeding from the right ear. Previously, she had been having bilateral intermittent foul smelling ear discharge for a year. Otoscope finding was insignificant as only blood seen. Computed tomography of temporal bone and magnetic resonance imaging of brain suggested locally aggressive cholesteatoma. Right ICA angiography showed pseudoaneurysm of petrous part of ICA. She underwent coil embolisation followed by bilateral modified radical mastoidectomy a month later. She recovered well after surgery and remained symptoms free. Conclusions: Pseudoaneurysm of petrous ICA as a complication of middle ear cholesteatoma is extremely rare. Spontaneous profuse bleeding maybe the only clinical presentation. Radiological imaging is important to diagnose and assist in treatment. Endovascular technique may be required, followed by surgical treatment for infection control.